Perlindungan Konsumen Dalam Transaksi Elektronik Kosmetik Tanpa Izin Edar - Vanessa Harum; Gatot P. Soemartono (Dinasti Review, 2024)
Buying and selling are activities that are commonly carried out by business actors and consumers. This research discusses buying and selling activities that occur on the Shopee platform. Trading cosmetics through online platforms such as Shopee has become a rapidly increasing trend in recent years. Although it provides easy access for consumers, especially in terms of shopping for beauty products, the existence of unlicensed cosmetic products sold illegally on the platform is a serious problem that affects consumer protection. As a business actor, you should follow the rules and standards set by BPOM. The case study found shows that the sale of unlicensed cosmetics on Shopee still faces challenges in monitoring and policing. Consumer protection should be the main focus in efforts to improve the safety and reliability of online shopping for cosmetics. Therefore, further action is needed from both Shopee and regulators to strengthen supervisory mechanisms, increase consumer education, and strengthen consumer protection rules to protect the public from the risks associated with purchasing illegal cosmetic products online.